More than a feeling: Autonomous sensory meridian response (ASMR) is characterized by reliable changes in affect and physiology. - Giulia Lara Poerio; Emma Blakey; Thomas J Hostler; Theresa Veltri (PLoS ONE)
Autonomous Sensory Meridian Response (ASMR) describes the experience of tingling sensations in the crown of the head, in response to a range of audio-visual triggers such as whispering, tapping, and hand movements. Public interest in ASMR has risen dramatically and ASMR experiencers watch ASMR videos to promote relaxation and sleep. Unlike ostensibly similar emotional experiences such as "aesthetic chills" from music and awe-inspiring scenarios, the psychological basis of ASMR has not yet been established. We present two studies (one large-scale online experiment; one laboratory study) that test the emotional and physiological correlates of the ASMR response. Both studies showed that watching ASMR videos increased pleasant affect only in people who experienced ASMR. Study 2 showed that ASMR was associated with reduced heart rate and increased skin conductance levels. Findings indicate that ASMR is a reliable and physiologically-rooted experience that may have therapeutic benefits for mental and physical health.